2005
DOI: 10.1160/th05-01-0067
|View full text |Cite
|
Sign up to set email alerts
|

Early antithrombotic and anti-inflammatory effects of simvastatin versus fenofibrate in patients with hypercholesterolemia

Abstract: The aim of the study was to determine whether a short-term treatment with simvastatin or fenofibrate may result in beneficial anti-inflammatory and antithrombotic effects in patients with high risk of coronary artery disease. In a randomized, double-blind study, we compared markers of inflammation, thrombin formation and platelet activation in patients with LDL cholesterol >130 mg/dl assigned to receive simvastatin (40 mg/d; n=20) or micronised fenofibrate (160 mg/d; n=22) for 28 days. Simvastatin, but not fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 41 publications
8
60
0
Order By: Relevance
“…Total inactivation of fVa after cleavage at Arg 506 and Arg 306 by APC (fVai 306,506 ) is associated with a 30 kDa fVa-HC fragment (fVa-HC 30 , residues 307 to 506). 7 The generation of this product of APC cleavage is greatly enhanced in AMI, an indication increased expression of the thrombin-thrombomodulin system either because of the enhanced thrombin availability, the enhanced expression of thrombomodulin and/or the endothelial protein C receptor (EPCR) or all of the above.…”
Section: Factor V Activation and Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Total inactivation of fVa after cleavage at Arg 506 and Arg 306 by APC (fVai 306,506 ) is associated with a 30 kDa fVa-HC fragment (fVa-HC 30 , residues 307 to 506). 7 The generation of this product of APC cleavage is greatly enhanced in AMI, an indication increased expression of the thrombin-thrombomodulin system either because of the enhanced thrombin availability, the enhanced expression of thrombomodulin and/or the endothelial protein C receptor (EPCR) or all of the above.…”
Section: Factor V Activation and Inactivationmentioning
confidence: 99%
“…In previous studies with this model we have reported the influence of aspirin and statins on thrombin generation [24][25][26][27][28][29] and platelet activation. 28,30 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, apart from that effect, fenofibrate has been considered a vascular anti-inflammatory and anti-thromboembolic drug through its decrease of plasma inflammatory cytokines and thromboembolic products, respectively [16,17]. Clinical trials of fenofibrate in patients with diabetes type 2 and with dyslipidemia report an improvement in impaired cardiovascular parameters associated to an improvement of endothelial function [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of fenofibrate in patients with diabetes type 2 and with dyslipidemia report an improvement in impaired cardiovascular parameters associated to an improvement of endothelial function [18,19]. This beneficial effect of fenofibrate on endothelial function seems to be mediated by an increase of endothelial NO release and/or bioavailability related to the inhibition of inflammatory pathways in the arterial wall, the antioxidant effect of fenofibrate and the enhancement of endothelial NOS (eNOS) expression and activity [13,16]. Endothelium-derived NO is an important mediator of cardiovascular protection through its regulatory effects on vascular tone, platelet aggregation, oxidative stress, leukocyte adherence and vascular smooth muscle cell proliferation [20].…”
Section: Discussionmentioning
confidence: 99%
“…In empirical reconstruction, simulated maximum thrombin levels (p<0.01) and rates (p<0.01) were 50% higher with ACS while the initiation phases of thrombin generation were shorter than in patients with stable CAD (Brummel-Ziedins et al, 2008). Elevated levels of thrombin derivatives are associated with clinical risk factors for stroke (Lane et al, 1983;Takano et al, 1991 Kłoczko et al, 1996), hyperglycaemia and hypercholesterolemia (Wada et al, 1992;Sanguigni et al, 2005;Undas et al, 2005).…”
Section: Prognostic Value Of Thrombin Generation In Cardiac Eventsmentioning
confidence: 99%